Phosphaturic mesenchymal tumor of the popliteal fossa: a case report and literature review - Wang, Yingjie; Liu, Shiwei; Li, Caixia; Song, Wenjing; Zhang, Yimin; Wang, Jun (Frontiers in Oncology, 2024)
Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome characterized by hypophosphatemia caused by excessive secretion of fibroblast growth factor-23 (FGF-23) by tumors. This leads to impaired bone mineralization and, ultimately, osteomalacia. The most common underlying cause is a phosphaturic mesenchymal tumor (PMT). Due to its rarity, nonspecific clinical presentation, and limited clinician awareness, TIO is frequently underdiagnosed or misdiagnosed. A 42-year-old man presented with persistent pain in the chest, lower back, knees, and ankles for more than six months, which had worsened in the preceding week. Laboratory tests revealed hypophosphatemia and abnormalities in markers of bone metabolism. Symptomatic treatment provided minimal improvement. The whole-body PET/CT scan subsequently identified a cystic and solid mass in the popliteal fossa of the right knee, with high somatostatin receptor expression. The tumor was surgically removed, and histopathological examination confirmed PMT. The patient’s blood phosphorus concentration returned to normal one week after surgery, and levels of other laboratory indicators gradually returned to normal. Although symptoms persisted during the first postoperative week, significant relief was noted by the second week. This case report highlighted the necessity of improving clinical recognition and management of TIO to ensure timely diagnosis and treatment.